Introduction of Late Pleistocene cultural material of an intermediate region: Paleolithic sites of Pion and Izeh plain between Central and Southern Zagros, Southwest Iran. (10th April 2019) - Jayez, Mozhgan; Molla Mirzai, Khadijeh; Niknami, Kamal Aldin
Abstract: The final phase of Late Pleistocene of Zagros Mountains has been introduced as Upper Paleolithic cultural material of Baradostian/Zagros Aurignacian, but differences between UP lithic industry in central and Southern Zagros has led to definition of another techno-complex in Southern Zagros named Rostamian. Another Late Paleolithic industry is Zarzian Epipaleolithic which is defined based on few absolute dating and excavated sites in the region. The nature of relationships and the territories of Late Paleolithic hunter-gatherers in the region is obscure. In this article an intermediate region between central and Southern Zagros with Late Paleolithic evidence is introduced based on surface survey of Izeh and Pion Plains in Southwestern Iran. Pion Plain in northwest of Izeh was surveyed in 2008 aiming at identifying the whole range of extant sites. 19 sites were dated to Late Paleolithic based on their surface lithic assemblages, and divided to minor and major sites regarding their surface material density and cultural deposits. Regarding different viewpoints about the homogeneity or variation of hominin groups during earlier phases of UP in the region, the lithic industry of Izeh and Pion lacks some of the most important typological elements of both UP and EP. Such a difference could be explained either as a chronological marker of the sites as belonging to later phase of Baradostian and earlier phase of Zarzian industry. On the other hand, it could be taken as an evidence of variation among techno-complexes in Late Paleolithic of Zagros Mountains. Chipped stone assemblages from the outer slopes of these caves and rock shelters present an industry from late UP and early EP which makes the Paleolithic sites with obvious cultural deposits inside them a proper candidate for excavations targeted at identification of the transitional processes from UP to EP in Zagros Mountains.